Développer la recherche et maintenir la professionnalisation - Marianne Blanchard (Cahiers de la Recherche sur l'Education et les Savoirs)
While internationalization and especially the Europeanization of higher education have forced French universities to become more professionally-oriented, the case of the Écoles Supérieures de Commerce (ESC-Business Schools) may at first sight appear as a counterexample to this trend. Indeed the development of international contacts has resulted in an « academic drift » for the ESC, with a growth in research activities, especially within the last decade. This evolution strengthens the historical tension within the field of management education between an academic and a professional norm. In a context of national and international reforms of higher education systems, the ESC-Business schools are striving to find a new balance between these two poles and to reconcile research activities and professional training.